2022
DOI: 10.3897/biorisk.17.77454
|View full text |Cite
|
Sign up to set email alerts
|

Pteromalid fauna (Hymenoptera, Pteromalidae) in oilseed rape (Brassica napus L.) fields in Bulgaria – species composition and perspectives for biological control

Abstract: Parasitoid wasps belonging to the family Pteromalidae are widespread and abundant members of the insect communities in the temperate regions of the world. As many other chalcids do, pteromalids serve as natural enemies of the pests in various crops and play an important role in the biological control of these harmful insects. Here we present the results of a field study in Bulgaria which was focused on the diversity of family Pteromalidae in ten oilseed rape fields. All samples were collected by sweep netting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other parasitoid species of these two pests were either not observed or observed in very low numbers. Todorov et al (2022) recently presented a checklist of the pteromalid fauna in Bulgarian oilseed rape fields and recorded 26 taxa, but, interestingly, did not find any Trichomalus species. Parasitoids of the cabbage flea beetle ( P. nemorum ) are represented only by Townesilitus bicolor , while other known species are absent or could not be determined at the species level, but only at the genus level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other parasitoid species of these two pests were either not observed or observed in very low numbers. Todorov et al (2022) recently presented a checklist of the pteromalid fauna in Bulgarian oilseed rape fields and recorded 26 taxa, but, interestingly, did not find any Trichomalus species. Parasitoids of the cabbage flea beetle ( P. nemorum ) are represented only by Townesilitus bicolor , while other known species are absent or could not be determined at the species level, but only at the genus level.…”
Section: Discussionmentioning
confidence: 99%
“… Petrović (2022) compared the parasitoid wasp fauna of the subfamily Aphidiinae from different European countries and found that only the Czech fauna had greater diversity (about 135 species) than the Serbian fauna (121 species), while other countries, such as Germany (109), the United Kingdom (96) and Norway (26), had fewer species, although the Czech fauna may simply be much better studied. To date, only Todorov et al (2022) have published a partial list of oilseed parasitoids for one Balkan country, Bulgaria and only for the family Pteromalidae . However, only two species ( Mesopolobus incultus and M. morys ) are recorded in both Bulgaria and Serbia, with the possible existence of several other taxa of the genera Mesopolobus and Pteromalus that are difficult to identify to species level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation